1999
DOI: 10.1007/bf03217934
|View full text |Cite
|
Sign up to set email alerts
|

Guideline of surgical management based on diffusion of descending necrotizing mediastinitis

Abstract: The mediastinal infection, the extent of which has been accurately determined by computed tomograms, necessitates radical cervicotomy followed by pleuromediastinal drainage. Situations where infection has spread to posterior medisatinum, particularly when it reaches in the level of the carina (descending necrotizing mediastinitis-type I), may not always require aggressive mediastinal drainage. In comparison, diffuse descending necrotizing mediastinitis-Type IIB demands complete mediastinal drainage with debrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
166
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(178 citation statements)
references
References 12 publications
1
166
0
11
Order By: Relevance
“…In addition to confirming a diagnosis of DNM and detecting complications, CT assessment of the extent of infection would aid in determining optimal management [29] and can assist in surgical planning and in assessing response to therapy [30]. In one series, a majority of follow-up CT examinations in DNM patients revealed unanticipated evidence of progression of disease requiring further intervention [30].…”
Section: Review: Descending Necrotising Mediastinitis E Weaver Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to confirming a diagnosis of DNM and detecting complications, CT assessment of the extent of infection would aid in determining optimal management [29] and can assist in surgical planning and in assessing response to therapy [30]. In one series, a majority of follow-up CT examinations in DNM patients revealed unanticipated evidence of progression of disease requiring further intervention [30].…”
Section: Review: Descending Necrotising Mediastinitis E Weaver Et Almentioning
confidence: 99%
“…In reported cases of DNM, successful surgical management involves a combination of cervical and mediastinal drainage with or without open thoracotomy [3,4,8,15,21,29,30,[36][37][38][39][40][41][42][43][44]. ENDO et al [29] proposed a classification scheme to facilitate management of DNM based on CT assessment of the extent of infection.…”
Section: Review: Descending Necrotising Mediastinitis E Weaver Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…(15) Other surgical approaches, such as clamshell thoracotomy, median sternotomy, anterolateral thoracotomy, and bilateral thoracotomy, have been proposed. (8)(9)(10)(11) Currently, minimally invasive intervention with the aid of video-assisted thoracoscopy is widely used. The first report of this surgical approach for the treatment of descending mediastinitis, describing the first cases treated with the combination of cervicotomy and videoassisted thoracoscopy, was published in 1997.…”
Section: Resultsmentioning
confidence: 99%
“…Despite abscess drainage and empiric broad-spectrum antibiotics, the patient developed a severe respiratory failure secondary to descending mediastinitis. A chest computed tomography (CT) scan showed that the infection was extending to the lower anterior and posterior mediastinum (type IIB DNM, according to Endo et al's classification) 2 (Fig. 1).…”
Section: Case Summarymentioning
confidence: 99%